Technology Matters, Are Pre-service Teachers Ready in Online Teaching Practicum? - Izza, Awwalia Fitrotin (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
The transition to online teaching has chaotic consequences for teachers and students, as many candidates are not ready for teaching duty. Unfortunately, several previous studies did not investigate pre-service teachers’ readiness to teach in online practicum. Additionally, the studies examining readiness, particularly on foreign language education programs through practicum, are limited. Therefore, the present study intends to investigate the pre-service foreign language program’s readiness to carry out teaching and learning processes in online practicum, especially in the ICT aspect. The study employs a qualitative research methodology. The setting of the study is an online practicum in a teacher education program in Semarang, Indonesia. The study participants are pre-service teachers taking online practicum, an estimated 130 participants based on the total population of the department selected. The data collection technique adopts an open-ended online survey conducted via Google Forms® and synchronous/ asynchronous interviews. The data collected from the questionnaire and interview is then analysed utilising a thematic analysis. The results of this research are supposed to contribute practically. All participants stated they were ready to have an online teaching practicum since they had already used it. They often use technology both for their daily needs and their studying needs.